Correction: Sun et al. C2C E-Commerce Platform Trust from the Seller’s Perspective Based on Institutional Trust Theory and Cultural Dimension Theory. Systems 2025, 13, 309 - Yulu Sun; Zhenhua Wang; Hongxiao Lyu; Qixing Qu (Systems)
In the published publication [...]